State dissociation moderates response to dialectical behavior therapy for posttraumatic stress disorder in women with and without borderline personality disorder - Kleindienst, Nikolaus; Schmahl, Christian; Bohus, Martin (European journal of psychotraumatology, 2016)
BackgroundPatients with posttraumatic stress disorder (PTSD) are prone to dissociation, which in theory should interfere with successful treatment. However, most empirical studies do not substantiate this assumption.ObjectiveThe primary objective was to test whether state dissociation predicts the success of an adaptation of dialectical behavior therapy designed for the treatment of patients with PTSD after childhood sexual abuse (CSA) (DBT-PTSD). We further explored whether the operationalization of dissociation as state versus trait dissociation made a difference with respect to prediction of improvement.MethodsWe present a hypothesis-driven post hoc analysis of a randomized controlled trial on the efficacy in patients with PTSD after CSA. Regression analyses relating pre-post improvements in the Clinician-Administered PTSD Scale (CAPS) and the Posttraumatic Diagnostic Scale (PDS) to dissociation were applied to the women who participated in the active treatment arm (DBT-PTSD). Multivariate models accounting for major confounders were used to relate improvements in both the CAPS and the PDS to (1) state dissociation as assessed after each treatment session and (2) trait dissociation as assessed at baseline.ResultsState dissociation during psychotherapy sessions predicted improvement after DBT-PTSD: patients with low state dissociation during treatment had a higher chance to show substantial improvement. This relation consistently emerged across subgroups of PTSD patients with and without borderline personality disorder. The operationalization of dissociation as state versus trait dissociation made a difference as improvement was not significantly predicted from trait dissociation.ConclusionsDissociation during treatment sessions may reduce success with trauma-focused therapies such as DBT-PTSD. Accordingly, clinical studies aimed at improving ways to address dissociation are needed.Highlights of the articleThe article investigates whether state dissociation during psychotherapeutic sessions moderates the success of an established treatment for PTSD.Patients were much more likely to substantially improve with respect to PTSD symptomatology if state dissociation during psychotherapeutic sessions was low.The article suggests that the relation between low dissociation and good response in highly symptomatic patients is stronger than previously thought.Future studies investigating the extent to which outcome might be improved when treating dissociation more vigorously than usually are necessary.